2022
DOI: 10.1109/tii.2022.3182326
|View full text |Cite
|
Sign up to set email alerts
|

Robust Synchronized Data Acquisition for Biometric Authentication

Abstract: Owing to its unique, concealment and easy customisation by combining different wrist and hand gestures, High-Density surface electromyogram (HD-sEMG) is recognised as a potential solution to the next generation biometric authentication, which usually adopts a wireless Body Sensor Network (BSN) to acquire the multi-channel HD-sEMG biosignals from distributed electrode arrays. For more accurate and reliable classification, biometric authentication requires the distributed biosignals to be sampled simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It is shown that when DO-PkCOs are applied to the BSN, an HD-sEMG signal with a high SNR value develops, which improves the performance of gesture categorization. [3] An acceptable smart glove that measures motion with an accelerometer and posture with a strain-sensitive resistive knit. In order to read data, extract features, and execute a pre-trained computational model, a microcontroller, a tiny customized PCB, and sensors are utilized.…”
Section: Literature Surveymentioning
confidence: 99%
“…It is shown that when DO-PkCOs are applied to the BSN, an HD-sEMG signal with a high SNR value develops, which improves the performance of gesture categorization. [3] An acceptable smart glove that measures motion with an accelerometer and posture with a strain-sensitive resistive knit. In order to read data, extract features, and execute a pre-trained computational model, a microcontroller, a tiny customized PCB, and sensors are utilized.…”
Section: Literature Surveymentioning
confidence: 99%
“…However, these protocols work well for crystal oscillator clocks, but can easily fail to realise synchronisation on low-accurate internal RC oscillator clocks. Note that the single-cluster topology is a popular solution for wireless BSN [1], [4]. This work possesses no need to study the time synchronisation of low-accuracy internal RC oscillator clocks in multi-hop wireless networks.…”
Section: A Related Workmentioning
confidence: 99%
“…The Industrial IoT (IIoT) provides various services (e.g. distributed data acquisition [1]) in numerous industry sectors, such as manufacturing and biometric authentication. These mission-critical IIoT applications have stringent requirements on real-time data transmission and control operation command.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, Data Compression (DC) technology is derived to satisfy the current requirements in terms of data quality, coding methods, data type, and applications to analyze the development of DC technology and its applications (1) . As storage and transmission capacity increases, the need for storage and transmission doubles.…”
Section: Introductionmentioning
confidence: 99%